Reality Model-Based Facility Management Framework for Existing Building - Duong, Hung Duy; Lin, Jacob J. (Frontiers in Built Environment, 2022)
Facility management (FM) is the most extended phase of the entire life cycle of buildings and incurs the highest expenses. However, limited quality drawings and historical data make information flow more complicated for many existing buildings and lead to inefficient FM. This research proposes a systematic and comprehensive reality point cloud model-based framework to support the FM process with feasible visual data collection. Specifically, this framework covers an end-to-end workflow of using a reality model to implement FM strategies, including visual data capture process for generating a reality model; FM information attachment in a reality model for issue queries; and information flow for issue tracking. The resulting reality model captures with critical and necessary FM data input can be used as an asset information model (AIM). We have also defined stakeholders' responsibilities in implementing FM and how the data are transferred, updated, and used within a reality point cloud-based AIM by stakeholders. The framework is evaluated by interviewing FM experts, and the results demonstrate that implementing the framework could improve the FM process's efficiency by using reality models.